2001
DOI: 10.1126/science.1057594
|View full text |Cite
|
Sign up to set email alerts
|

Redox State of Mars' Upper Mantle and Crust from Eu Anomalies in Shergottite Pyroxenes

Abstract: The oxidation state of basaltic martian meteorites is determined from the partitioning of europium (Eu) in their pyroxenes. The estimated redox conditions for these samples correlate with their initial neodymium and strontium isotopic compositions. This is interpreted to imply varying degrees of interaction between the basaltic parent melts, derived from a source in the martian mantle, and a crustal component. Thus, the mantle source of these martian basalts may have a redox state close to that of the iron-wüs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
243
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(259 citation statements)
references
References 33 publications
(39 reference statements)
15
243
1
Order By: Relevance
“…Even though the bulk Fe 3C / P Fe content of the mantle is relatively low (2-3%), oxygen fugacities calculated from ferric-ferrous equilibria involving spinel are high because f O 2 is proportional to the activity of Fe 2 O 3 in spinel (O'Neill et al 1993b). At higher pressures, this is no longer the case and ferric Fe becomes dissolved in minerals such as garnet, which have larger modal abundances (O'Neill et al 1993b; ( Wadhwa 2001;Herd et al 2002) and for Lunar basalts (Papike et al 2004) are also shown. IW, iron-wüstite; FMQ, fayalite-magnetite-quartz; NNO, Ni-NiO redox buffer.…”
Section: The Redox State Of the Present-day Mantlementioning
confidence: 92%
See 1 more Smart Citation
“…Even though the bulk Fe 3C / P Fe content of the mantle is relatively low (2-3%), oxygen fugacities calculated from ferric-ferrous equilibria involving spinel are high because f O 2 is proportional to the activity of Fe 2 O 3 in spinel (O'Neill et al 1993b). At higher pressures, this is no longer the case and ferric Fe becomes dissolved in minerals such as garnet, which have larger modal abundances (O'Neill et al 1993b; ( Wadhwa 2001;Herd et al 2002) and for Lunar basalts (Papike et al 2004) are also shown. IW, iron-wüstite; FMQ, fayalite-magnetite-quartz; NNO, Ni-NiO redox buffer.…”
Section: The Redox State Of the Present-day Mantlementioning
confidence: 92%
“…The rise in the redox state of the mantle since core formation, therefore, is more accurately reflected in the Fe 3C / P Fe of the upper mantle (or better still the O/Fe ratio), which is in the range of 2-3 per cent in the present-day mantle (Canil & O'Neill 1996), but would have been much lower than this when in equilibrium with metallic Fe. In figure 2, estimates for the f O 2 of the Martian mantle from SNC meteorites (Wadhwa 2001;Herd et al 2002) and the f O 2 of lunar basalts (Papike et al 2004) are also shown. The simplest explanation would seem to be that these bodies did not undergo the same level of mantle oxidation as experienced by the Earth.…”
Section: The Evolution Of Mantle F Omentioning
confidence: 99%
“…These variations suggest distinct igneous histories for the two meteorites. Mineral compositions and an absence of xenocrysts suggest that QUE 94201 is a bulk melt and the result of closed system fractional crystallization under relatively low fO 2 conditions (0.3 to 1.0 log units below IW buffer; Mikouchi et al, 1998;Wadhwa, 2001;Kring et al, 2003). QUE 94201 is likely derived from a mantle that has already undergone 4 to 5 episodes of partial melting and extraction of an alkali and light REE-enriched melt (Borg et al, 1997).…”
Section: Comparing the Two Datasetsmentioning
confidence: 99%
“…Wadhwa (2001) Nd ratios and suggested that the basalts formed in a reducing environment in the upper mantle and were subsequently oxidized by assimilation of water-rich crustal material. Similarly, Herd et al (2002) determined the oxygen fugacity from the nature of Fe-Ti oxides in several Martian basalts and also suggested that the most reduced system was representative of the primary magma, and that the more oxidized basalts may have been altered by assimilated material that contained significant amounts of water.…”
Section: William V Boyntonmentioning
confidence: 99%